2021
DOI: 10.3389/fmicb.2021.796191
|View full text |Cite
|
Sign up to set email alerts
|

Different Responses of Soil Environmental Factors, Soil Bacterial Community, and Root Performance to Reductive Soil Disinfestation and Soil Fumigant Chloropicrin

Abstract: Reductive soil disinfestation (RSD) and soil fumigant chloropicrin (SFC) are two common agricultural strategies for the elimination of soil-borne pathogens. However, the differences in soil environmental factors, soil bacterial microbiome, and root performance between SFC and RSD are poorly understood. In this study, three soil treatments, untreated control (CK), SFC with 0.5 t⋅ha–1 chloropicrin, and RSD with 15 t⋅ha–1 animal feces, were compared. We evaluated their effects on soil environmental factors, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Flavisolibacter is an important iron-reducing agent, converting Fe 3+ to Fe 2+ both directly and indirectly under anaerobic conditions, and Fe 2+ accumulation significantly inhibits plant pathogen growth ( 50 , 56 ). Sphingomonas is a microorganism that has good environmental adaptability and tolerance and can degrade polycyclic aromatic hydrocarbons and phenols ( 31 ). Sphingomonas was positively correlated with manganese oxidation and chloroplasts but negatively correlated with aromatic compound degradation or nitrate reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavisolibacter is an important iron-reducing agent, converting Fe 3+ to Fe 2+ both directly and indirectly under anaerobic conditions, and Fe 2+ accumulation significantly inhibits plant pathogen growth ( 50 , 56 ). Sphingomonas is a microorganism that has good environmental adaptability and tolerance and can degrade polycyclic aromatic hydrocarbons and phenols ( 31 ). Sphingomonas was positively correlated with manganese oxidation and chloroplasts but negatively correlated with aromatic compound degradation or nitrate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was conducted using primers 338F/806R and ITS1F/ITS2R for amplification. The protocols described by Zhan et al ( 31 ) and Tan et al ( 24 ) were used for the amplification of bacterial 16S rRNA and fungal ITS genes and analysis of PCR product purity.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the specific effects of biostimulants may vary depending on the type of treatment and the time point during the growing season at which measurements are taken. In a recent study (66), it was suggested that the use of biostimulants, such as the Bacillus-species inoculant based on eight strains used in our study, could promote the growth and diversity of beneficial microorganisms in the soil, potentially leading to improved soil health and plant growth. Our findings support this notion, since the application of biostimulant in non-fumigated soils (T2 treatment) promotes a persistent high proportion of Firmicutes in T2 plots.…”
Section: Treatments Effects On Soil Bacterial Community Compositionmentioning
confidence: 94%
“…The biomass (fresh weight and dry weight) of each group was measured. In addition, the root activity was determined by the 2,3,5-triphenyl tetrazolium chloride (TTC) method ( Zhan et al, 2021 ). Root activity is expressed as the mass of triphenyl formazan produced per gram of fresh root per hour.…”
Section: Methodsmentioning
confidence: 99%